Pengendalian Kualitas Produksi Agar-agar di PD.Restu - Chandrahadinata, Dody; Sa’adudin, Dedi; Nisa, Neng (Jurnal Kalibrasi, 2025)
PD.Restu is a company engaged in the production of gelatin. In its production activities, the company always experiences problems related to the quality of the products produced which are caused by a lack of attention to methods, machines and materials in the manufacturing process. The level of defects in the production process still exceeds the specified limits, so quality control is necessary. PD.Restu applies a rework system to damaged products, in which case this will of course require additional costs such as additional material costs, operator costs and rework costs. PD.Restu has many defective products that do not comply with company specifications, the average total defects in gelatin products for the period January-June 2023 is 8%. The aim of this research is to find out the factors that cause the largest defects in gelatin products. This research uses a statistical process control (SPC) approach with check sheet tools, Pareto diagrams, control charts and fishbone diagrams. The research results show that the production process is not yet under control. There are 3 types of defects in gelatin products, namely syneretic defects 45%, non-resilient texture 34% and rough surface 21%. To find out several factors that cause defects, use a fishbone diagram with the results that there are several factors, namely humans, machines and methods. Next, the FMEA stage is to determine the priority scale for the size of the RPN. Based on the results of the RPN, it produces suggestions for improvements by providing training to operators, providing SOPs and evaluating unskilled employees. Then analyze the rework costs for 6 months that arise based on defective products, where there are additional costs from several factors, namely operator costs IDR 35,498,800 and replacement material costs IDR 90,970,594, with total production of IDR 67,480 then the rework cost per 1 bag is IDR 24,325.